2021
DOI: 10.3389/fonc.2021.766072
|View full text |Cite
|
Sign up to set email alerts
|

A New Risk Score Based on Eight Hepatocellular Carcinoma- Immune Gene Expression Can Predict the Prognosis of the Patients

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the malignant tumors with high morbidity and mortality worldwide. Immunotherapy has emerged as an increasingly important cancer treatment modality. However, the potential relationship between immune genes and HCC still needs to be explored. The purpose of this study is to construct a new prognostic risk signature to predict the prognosis of HCC patients based on the expression of immune-related genes (IRGs) and explore its potential mechanism.MethodsWe analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Compared to these gene signatures, our gene signature had the following features: first, our gene signature was established based on five GRGs that were independently associated with HCC prognosis. Considering the vital role of glycolysis in tumor development and progression, our gene signature is surely to have a better predictive performance than the previous predictive models [ 58 61 ]; second, some of the previous gene signatures lacked external validation using other datasets [ 60 ], consequently, we used the ICGC-LIRI—JP as an external validation cohort to verify the results of this study, which showed that the gene signature had good predictive performance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Compared to these gene signatures, our gene signature had the following features: first, our gene signature was established based on five GRGs that were independently associated with HCC prognosis. Considering the vital role of glycolysis in tumor development and progression, our gene signature is surely to have a better predictive performance than the previous predictive models [ 58 61 ]; second, some of the previous gene signatures lacked external validation using other datasets [ 60 ], consequently, we used the ICGC-LIRI—JP as an external validation cohort to verify the results of this study, which showed that the gene signature had good predictive performance.…”
Section: Discussionmentioning
confidence: 91%
“…Many gene signatures have been constructed to predict HCC patient survival [ 58 61 ]. Compared to these gene signatures, our gene signature had the following features: first, our gene signature was established based on five GRGs that were independently associated with HCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…They identified nine lnRNAs closely related to disease-free survival which could be validated as potential biomarkers to predict HCC recurrence [126]. Similarly, Ye et al compared gene expression data of HCC patients and normal tissue samples and selected differentially expressed immune related genes in HCC samples, and constructed an immune-related gene signature based on eight genes such as CHGA, RAETIE, FGF9, GIP, NROB1, IL20RA, ESRRG, and GNNRH2 to predict the HCC prognosis [127]. Another research team designed 15 immune-related gene signatures as a prognostic model for an HCC-based TGCA dataset using Cox regression analysis [128].…”
Section: Natural Killer Cellsmentioning
confidence: 99%